Use of Nd:YAG laser to recanalize occluded Cypass Micro-Stent in the early post-operative period - Perez, Claudio I. (Elsevier Inc., 2018)
Purpose: To report the first case of Neodymium Yttrium Aluminum Garnet (Nd:YAG) laser use to recanalize aCyPass occluded with a clot in the early postoperative follow-up.Observations: A 66 year-old woman with primary open angle glaucoma and cataract received combined cataractsurgery plus CyPass in the right eye. Surgery was uneventful, however, there was a small amount of hyphemarelated to bleeding around the site of Cypass insertion. Intraocular pressure (IOP) was between 6 and 7 mmHg inthe first week on no glaucoma medications. At the second postoperative week, IOP jumped to 30 mmHg and aclot was observed obstructing the CyPass lumen. We disrupted the clot with a single shot from a Nd:YAG laser.Twenty minutes after the laser, the IOP was 8 mmHg. CyPass was recanalized without complications. IOP was11 mmHg at 1 month postoperatively with timolol 0.5% twice a day.Conclusions and importance: It is important to perform gonioscopy to evaluate for CyPass obstruction in cases ofIOP spike. Nd:YAG laser may be a useful approach to recanalize the CyPass in the early postoperative follow-up